CO2 low‐level laser therapy has an early but not delayed pain effect during experimental tooth movement. (June 2017) - Deguchi, T.; Kim, DG.; Kamioka, H.
Structured Abstract: Objectives: To test the hypothesis that the use of low‐level laser therapy (LLLT) reduces elevated pain by controlling the release of neurochemicals during orthodontic tooth movement. Setting and Sample Population: Department of Orthodontics and Dentofacial Orthopedics, Okayama University. Sixty‐five Sprague Dawley rats were subjected to tooth movement and LLLT. Materials and Methods: Adult Sprague Dawley rats were used in this study. Groups included day 0 controls, irradiation only controls and with or without irradiation sacrificed at 1, 3, 5, 7 and 14 days after tooth movement (n=5 each, total n=65). Tooth movement was achieved by insertion of an elastic module between molar teeth. Immunohistochemistry for CD‐11b, GFAP and c‐fos in the brain stem was performed. Stains were quantified by constructing a three‐dimensional image using IMARIS, and counted using NEURON TRACER and WinROOF software. Two‐way ANOVA followed by a Tukey's post hoc test ( P <.05) was used for statistical comparison between groups. Results: C‐fos expression was significantly increased at one and three days after tooth movement. LLLT significantly diminished this increase in c‐fos expression only at one day after tooth movement CD‐b11 and GFAP expression also significantly increased after tooth movement. No significant change was observed for CD‐11b and GFAP expression in the central nervous system upon LLLT. Conclusion: Low‐level laser therapy may reduce early neurochemical markers but have no effect on delayed pain neurochemical markers after tooth movement.